2021
DOI: 10.3390/ijms22158053
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of LSEC in Post-Hepatectomy Liver Regeneration and Failure

Abstract: Liver sinusoids are lined by liver sinusoidal endothelial cells (LSEC), which represent approximately 15 to 20% of the liver cells, but only 3% of the total liver volume. LSEC have unique functions, such as fluid filtration, blood vessel tone modulation, blood clotting, inflammatory cell recruitment, and metabolite and hormone trafficking. Different subtypes of liver endothelial cells are also known to control liver zonation and hepatocyte function. Here, we have reviewed the origin of LSEC, the different subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 117 publications
1
17
0
Order By: Relevance
“…In WT mouse livers, the spatiotemporal expression of HMGB2 was strongly correlated with active cell proliferation, especially at 36–72 h after PHx. Our results also confirmed that hepatocytes are the first dividing cells, followed by proliferation of cholangiocytes and endothelial cells 21 , 22 . The expression of Ki-67 is a reliable marker of dividing cells, and it is not expressed in G 0 phase 23 .…”
Section: Discussionsupporting
confidence: 85%
“…In WT mouse livers, the spatiotemporal expression of HMGB2 was strongly correlated with active cell proliferation, especially at 36–72 h after PHx. Our results also confirmed that hepatocytes are the first dividing cells, followed by proliferation of cholangiocytes and endothelial cells 21 , 22 . The expression of Ki-67 is a reliable marker of dividing cells, and it is not expressed in G 0 phase 23 .…”
Section: Discussionsupporting
confidence: 85%
“…This could be indirect evidence for possible expansion of those existing drug markets. However, hepatocytes behave quite differently in terms of polarity characteristics in the traditional in vitro 2D culture condition [ 39 , 40 ]. An in vitro collagen sandwich system sheds light on the dilemma, in which primary hepatocytes are isolated and cultured inside two layers of collagen, showing the exciting ability to re-establish cell polarity and maintain hepatic functions [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…LSECs produce mitotic substances, specifically IL-6, hepatocyte growth factor and VEGF ( 152 ). Direct adhesion between platelets and LSECs induces IL-6 release, in turn, leading to hepatocyte growth factor secretion from hepatic stellate cells promoting hepatocyte regeneration in vitro ( 153 ).…”
Section: The Role Of Platelets In Resolution Of Inflammationmentioning
confidence: 99%